2009
DOI: 10.1074/jbc.m109.013342
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of Nucleostemin in the Maintenance of Nucleolar Architecture and Integrity of Small Nucleolar Ribonucleoproteins and the Telomerase Complex

Abstract: Nucleostemin (NS) is a nucleolar protein involved in the regulation of cell proliferation. Both overexpression and knockdown of NS increase the activity of the tumor suppressor protein p53, resulting in cell cycle arrest. In addition, NS regulates processing of pre-rRNA and consequently the level of total protein synthesis. Here, we describe a previously uncharacterized function of NS in the maintenance of the tripartite nucleolar structure as well as the integrity of small nucleolar ribonucleoproteins (snoRNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 41 publications
(49 reference statements)
2
26
1
1
Order By: Relevance
“…However, cells in which nucleostemin had been knocked down for 6 days displayed a substantial reduction (75%) in their nucleoplasmic 5-EU differential signal compared with siScr-treated cells. Finally, in contrast to a previous report (Romanova et al, 2009b) showing that nucleostemin depletion causes a dispersion of the dense fibrillar component (DFC) of nucleolar structure, which is defined by the protein fibrillarin, we found no discernible changes in the fibrillarin-labeled DFC structure in cells in which nucleostemin was knocked down for 2 days (Fig. 3C1), but a disorganized DFC structure was apparent in some cells after a 6-day knockdown (Fig.…”
Section: Dna Damage In S-phase Cells Is An Early Event After Nucleostcontrasting
confidence: 54%
See 1 more Smart Citation
“…However, cells in which nucleostemin had been knocked down for 6 days displayed a substantial reduction (75%) in their nucleoplasmic 5-EU differential signal compared with siScr-treated cells. Finally, in contrast to a previous report (Romanova et al, 2009b) showing that nucleostemin depletion causes a dispersion of the dense fibrillar component (DFC) of nucleolar structure, which is defined by the protein fibrillarin, we found no discernible changes in the fibrillarin-labeled DFC structure in cells in which nucleostemin was knocked down for 2 days (Fig. 3C1), but a disorganized DFC structure was apparent in some cells after a 6-day knockdown (Fig.…”
Section: Dna Damage In S-phase Cells Is An Early Event After Nucleostcontrasting
confidence: 54%
“…In this respect, it is noteworthy that effects on ribosome synthesis have been observed following two rounds of RNAi-mediated nucleostemin knockdown over a period of 5 days (Romanova et al, 2009a;Romanova et al, 2009b). Motivated by the recent discovery of a role for nucleostemin in protecting telomeres and the genome integrity of stem and progenitor cells (Hsu et al, 2012;Lin et al, 2013;Meng et al, 2013;Yamashita et al, 2013), we began to consider whether the accumulation of DNA damage, rather than impaired ribosome production, is actually the initial event following nucleostemin depletion.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies based on fluorescence observations have demonstrated that various nucleolar proteins, such as fibrillarin and nucleophosmin (B23), tagged to fluorescent proteins are functional and can be used as markers for observing changes in morphology of the nucleolus in live cells. In addition to fibrillarin and B23, NS, which is a key nucleolar protein in eukaryotes, has multiple functions and also contributes to the nucleolus architecture (12,13,36). It has been demonstrated that the different mobility of nucleolar proteins and the exchange rate between the nucleoplasm and the nucleolus under normal and ActDtreated conditions are related to their functional roles in ribosome biogenesis (13).…”
Section: Molecular Accessibility and Mobility Of Gfp N And Gfp-la Insmentioning
confidence: 99%
“…siRNA to nucleophosmin caused major distortion in nuclear and nucleolar structure. 45,46 siRNA to Nop25 caused nucleolar fragmentation. 47 Nucleostemin knockdown caused cell cycle arrest 48,49 and modified the internal pattern of the DFC, causing the loosening of snoRNP clusters.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…47 Nucleostemin knockdown caused cell cycle arrest 48,49 and modified the internal pattern of the DFC, causing the loosening of snoRNP clusters. 46 USP36 depletion GAA TTC TTG TAC TTT AAC TTT CTT GGA; 1-193 aa, 581 bp, anti-sense: ATA GAA TTC ATG AAG GCT TGT GCT GCT TGT;…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%